Bemisia tabaci, Brevicoryne brassicae and Thrips tabaci abundance on Brassica oleracea var. acephala - Leite, Germano Leão Demolin; Picanço, Marcelo; Jham, Gulab Newandram; Moreira, Márcio Dionízio (Pesquisa Agropecuaria Brasileira, 2005)
Kale Brassica oleracea var. acephala is attacked by whitefly Bemisia tabaci, aphid Brevicoryne brassicae and Thrips tabaci. One of the main reasons for extensive insecticide application is the lack of information about factors that control insect population. The objectives of this study were to investigate the relationships between predators and parasitoids, organic compound leaves, levels of leaf nitrogen and potassium, total rainfall, relative humidity, sunlight and median temperature on the abundance of whitefly, aphid, and thrips in kale genotype "Talo Roxo". The beating tray method, direct counting and magnifying lens were used to estimate the number of these pests, predators and parasitoids. Median temperature, sunlight and relative humidity correlated to the amount of leaf nonacosane, which in turn was associated with aphids population increase. A tendency in the reduction of aphids and thrips populations with increase in total rainfall was observed. The whitefly can be a harmful pest in kale producing regions of higher temperature and smaller rainfall. In regions which present moderate temperature, where there is a high incidence of aphids, genotype with low leaf wax content should be chosen. Natural enemies, especially the parasitoid Adialytus spp., can control agents of the aphids population in kale.